Enhanced thermoelectric performance of poly(3-substituted thiophene)/single-walled carbon nanotube composites via polar side chain modification. (20th October 2020) - Hao, Liping; Kang, Jiayuan; Shi, Jiale; Xu, Jinjia; Cao, Jianyun; Wang, Lei; Liu, Yi; Pan, Chengjun
Abstract: Composites of conducting polymers and single-walled carbon nanotubes (SWCNT) are promising thermoelectric materials but require further performance enhancement for practical application. Inspired by the improved compatibility between conducting polymer and small molecule dopants via polar side chain modification, we propose in this work a high performance composite comprising polar side chain engineered conducting polymer and SWCNT. In detail, two kinds of polythiophene/SWCNT composites bearing different side chains called poly (3-hexylthiophene) (P3HT) and poly (thiophene-3-[2-(2-methoxy-ethoxy)ethoxy]-2, 5-diyl) (PMEET) were prepared and composited with SWCNT. Molecular simulations revealed that, compared with P3HT, PMEET bearing polar side chains has better backbone planarity and a narrower band gap with a less deep HOMO level. These properties led to enhanced interactions between PMEET and SWCNT, evidenced by UV–vis absorption and Raman spectroscopies. The optimized PMEET/SWCNT composite film showed a high electrical conductivity of 699 S cm −1, which is three times higher than that of P3HT/SWCNTs (219 S cm −1 ). This enhanced electrical conductivity of PMEET/SWCNT led to a twice-higher power factor (121 μW m −1  K −2 ) than that of P3HT/SWCNT composite film (65 μW m −1  K −2 ). This work provides a feasible platform for optimizing the thermoelectric property of conducting polymer composites via side-chain engineering. Graphical abstract: Image 1 Highlights: Polythiophenes with different side chains (P3HT and PMEET) were prepared. Strong interaction between polythiophene with polar side chain and SWCNT was proved. The PF value of PMEET/SWCNT composites reaches up to 121 μW m −1  K −2 . The PF value of PMEET/SWCNT composite is twice that of P3HT/SWCNT composite.